A homogeneous photoelectrochemical hydrogen sulfide sensor based on the electronic transfer mediated by tetrasulfophthalocyanine. Issue 10 (6th May 2020) - Wang, Xinyang; Zhao, Huanan; Chen, Zhonghui; Luo, Fang; Guo, Longhua; Qiu, Bin; Lin, Zhenyu; Wang, Jian
Abstract : A homogeneous photoelectrochemical sensor for H2 S detection based on the electronic transfer mediated by [Fe(iii )PcS4 ] + was developed with an un-modified photoelectrode. Abstract : Hydrogen sulfide (H2 S) can regulate a variety of physiological functions, and the development of sensitive H2 S detection methods is a requirement. In this study, a homogeneous photoelectrochemical (PEC) sensor for H2 S detection was constructed based on the energy level matching of iron(iii ) phthalocyanine-4, 4′, 4′′, 4′′′-tetrasulfonic acid ([Fe(iii )PcS4 ] + ) and n-GaN. The photocurrent of n-GaN could be suppressed by monomeric [Fe(iii )PcS4 ] + since the photogenerated electrons in the conduction band (CB) of n-GaN could be injected into the LUMO of [Fe(iii )PcS4 ] + . Under weak alkaline conditions, monomeric [Fe(iii )PcS4 ] + can be converted to [Fe(i )PcS4 ] − after reacting with H2 S with high selectivity. The LUMO of [Fe(i )PcS4 ] − was higher than the CB of n-GaN, so the photogenerated electrons in the LUMO of [Fe(i )PcS4 ] − could be injected back into the CB of n-GaN. The electron–hole pair recombination could be hindered, which resulted in the recovery of the system photocurrent. In the H2 S concentration range of 10.0 nM–50.0 μM, a linear relationship was obtained between the photocurrent and the logarithm of H2 S concentration with a detection limit of 3.40 nM. The proposed method avoids tedious electrode modifying procedures required in conventional PEC sensors and it was applied to detect extracellular H2 S in rat brains coupled with microdialysis.